(untitled) (Texas Journal of Agriculture and Biological Sciences, 2026)
In this article, the main composition of microorganisms isolated from mastitis of dairy cows is Candida+Staphylococcus aureus+Streptococcus agalaetiae fungi and staphylococci; Staphylococcus aureus+Streptococcus agalaetiae; Streptococcus dysgalaetiae+Staphylococcus haemolyticus; Staphylococcus epidermidis+Escherichia staphylococci and streptococci; Candida species Coli+fungi; Staphylococcus epidermidis+Clostridium perfringens are staphylococci and clostridia, including Streptococcus agalaetiae (27%), Staphylococcus aureus, Staphylococcus hominis, Staphylococcus saprophyticus, Escherichia Coli (4%), Streptococcus dysgalaetiae, Clostridium perfringens (3%).